Methodological features of the analysis and estimation of economic security based on the state financial regulation of health care of the Russian Federation - E. B. Krylova; O. V. Kalashnikova (Путеводитель предпринимателя, 2020)
The article discusses the methodological features of analyzing and assessing economic security depending on the degree of influence of state financial regulation in the health sector, including principles, methods for analyzing the effectiveness ofthe mechanism for financial support of medical organizations and the algorithm for evaluating safety under the influence of the factor of preserving public health and using modern tools. The influence of such factors as human potential and the «health of the nation» is considered as a counterbalance to global challenges in the new conditions.